PELAKSANAAN KURIKULUM MERDEKA DALAM MEMBINA KARAKTER SISWA PADA PELAJARAN PAI DAN BUDI PEKERTI - Nurjanah, Dewi; Abdurrahmansyah, Abdurrahmansyah; Fauzi, Muhamad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to analyze the implementation of the independent curriculum in relation to character learning in PAI and Budi Pekerti subjects at SD Negeri 127 Palembang, the obstacles faced by PAI and Budi Pekerti teachers at SD Negeri 127 Palembang in implementing character education in the implementation of the independent curriculum, and analyze the impact resulting from the implementation of the independent curriculum in improving student character. The type of research used in this research is field research with the location at SD Negeri 127 Palembang. This research uses a case study approach with the data collection techniques being observation, in-depth interviews and documentation. Testing the credibility of the data is triangulation, and diligent observation. While analyzing the data using the stages of reducing data, displaying data, and verifying data. The results of this study show that in fostering student character through this independent curriculum, teachers link it to each lesson. in its implementation, there are several difficulties faced by the school, especially by PAI and Budi Pekerti teachers, namely difficulty in making teaching modules and lack of communication with the principal. Nevertheless, the implementation of this independent curriculum has a positive impact on student character through learning that is integrated with character values where students can understand, internalize, and apply these values in their daily lives. This helps them to develop a positive and responsible personality.